Development of Learning Tools based on Food Security to Build Scientific Attitude of Undergraduate Students - Suryani, Dwi Indah; Berlian, Liska; Rachmawati, Dinda; Laraswati, Mila Dewi (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2020)
This study aimed to develop learning tools that are proper to use, where the learning tools developed are based on food security in a food chemistry course to increase the scientific attitude of undergraduate students of the science teacher candidates. The type of research used in this study is Research and Development. The proper learning tools are conducted by testing the validity and effectiveness of the product. This research was conducted on 23 undergraduate students at the Department of Science Education, Faculty of Teacher Training and Education, Universitas Sultan Ageng Tirtayasa, Indonesia by using students’ scientific attitude questionnaire responses and the students’ questionnaire responses to learning tools. The analysis results stated that food security-based learning tools which be developed were proper for using in food chemistry course because after going through the stages of validation, small groups trial, and product revision, the validity criteria of learning tools are in very valid criteria and based on the effectiveness test of learning tools are in very effective criteria. Food security-based learning tools developed can also build the scientific attitude of undergraduate students on very good criteria. Then it is concluded that learning tools developed are proper to use. The next will be implemented in the large-scale trial to get the final product of food security-based learning tools.